Receptor for advanced glycation end products (RAGE)--soluble form (sRAGE) and gene polymorphisms in patients with breast cancer - Tesařová, Petra; Kalousová, Marta; Jáchymová, Marie; Mestek, Oto; Petruželka, Luboš; Zima, Tomáš (Cancer investigation, 2007)
Receptor for advanced glycation end products (RAGE) may be involved in the pathogenesis of the cancer progression and metastasis. Pathological effects mediated via RAGE are physiologically inhibited by soluble RAGE (sRAGE), so the higher sRAGE levels may confer the patients with cancer with better outcome. The aim was to study sRAGE and RAGE gene polymorphisms in patients with breast cancer. The authors studied sRAGE and RAGE polymorphisms in 120 patients with breast cancer (subdivided based on the clinical stage, histologic grading, expression of hormonal and Her2/neu receptors) and in 92 healthy controls. Despite higher serum concentrations of AGEs, serum concentrations of sRAGE were lower in patients with breast cancer compared to healthy controls (1581 +/- 777 versus 1803 +/- 632 ng/mL, p < 0.05). Serum levels of sRAGE were higher in patients with advanced breast cancer (stage III), lower grade and positive estrogen receptors, and intermediate positivity of Her2/neu receptors and were also influenced genetically (Gly82Ser and 2184 AG polymorphisms of the RAGE gene). Decreased sRAGE levels in patients with breast cancer may contribute to the progression of the disease. Patients with better outcome (low grade and positive estrogen receptors) have higher sRAGE levels. Progression of the disease, may, however, increase sRAGE levels, possibly as a compensatory mechanism to counteract further progression.
Keywords: Receptors, Estrogen; financování organizované; dospělí; nádory prsu; Female; Adult; ženské pohlaví; lidé; Receptors, Immunologic; Glycation End Products, Advanced; Breast Neoplasms; receptory pro estrogeny; receptory imunologické; Receptor, ErbB-2; Financing, Organized; receptor erbB-2; Aged; polymorfismus genetický; produkty pokročilé glykace; lidé středního věku; senioři; Polymorphism, Genetic; Middle Aged; Humans